PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. WAHANA OTTOMITRA MULTIARTHA FINANCE DI TANGERANG SELATAN - Noval Abdi Ramadhan; Komarudin Komarudin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to explore the impact of social media usage on brand awareness within the context of digital marketing at Nguyup, a micro, small, and medium enterprise (MSME) located in South Tangerang. The rapid development of digital technology, particularly social media, has become a strategic tool for businesses to build brand awareness and reach wider consumer markets at relatively low cost. This research employs a qualitative descriptive method. Data were collected through observation, in-depth interviews, and documentation involving internal parties of Nguyup who are directly engaged in marketing activities.The findings indicate that social media platforms, especially Instagram and TikTok, play a significant role in increasing Nguyup’s brand awareness through creative, consistent, and interactive content. The digital marketing strategies implemented contribute to improving brand recognition, expanding market reach, and strengthening relationships with consumers. However, the study also identifies challenges such as intense competition and the limited awareness of the brand among certain consumer segments. Therefore, more focused and innovative digital marketing strategies are required to sustainably enhance brand awareness.